2018
DOI: 10.1590/1678-98652018000100007
|View full text |Cite
|
Sign up to set email alerts
|

The role of educator in food and nutrition by health professionals in the context of Family Health Care

Abstract: Objective This study aimed to understand the role of health professionals in educational groups that have food and nutrition as their theme. Methods Qualitative research was conducted in the city of São Paulo, with professionals from the Family Health Strategy. Interviews were conducted to understand the professionals’ perceptions of the roles played in groups. These were analyzed using the Discourse of the Collective Subject technique. The groups’ observations on the performance of the professionals in their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
0
0
2
Order By: Relevance
“…Similar to other studies 28,29 , a weakness identified in implementing the PPAAS was a declining client adherence to the Program over time, despite the active search. PPAAS adherence was 61.9%, meaning that 38.1% of the clients who started the Program still needed to finish it.…”
Section: Discussionsupporting
confidence: 56%
“…Similar to other studies 28,29 , a weakness identified in implementing the PPAAS was a declining client adherence to the Program over time, despite the active search. PPAAS adherence was 61.9%, meaning that 38.1% of the clients who started the Program still needed to finish it.…”
Section: Discussionsupporting
confidence: 56%
“…De forma semelhante a outros estudos 28,29 , uma fragilidade identificada na implantação do PPAAS foi a redução da adesão dos usuários ao Programa com o tempo, apesar da busca ativa. A adesão ao PPAAS foi 61,9%, ou seja, 38,1% dos usuários que iniciaram o Programa, não chegaram ao final.…”
Section: Discussionunclassified
“…O uso dos dados de consumo alimentar como parte do SISVAN Web, a promoção da alimentação adequada e saudável em ações coletivas e atividades relacionadas às deficiências de ferro e vitamina A foram relatadas por poucos dos profissionais que participaram do presente trabalho, assemelhando-se a achados reportados em outras pesquisas com enfoques similares 29,31,43 e por meio da avaliação de programas do campo da nutrição [44][45][46][47] . O cuidado nutricional para crianças com necessidades alimentares específicas também mostrou-se deficiente, aspecto que não tinha sido abordado na literatura 48 .…”
Section: Discussionunclassified